Keputusan Mahasiswa Menggunakan Jasa Perbankan Syariah : Apakah Pengaruh Literasi Keuangan Syariah ? - Elvinda Yulianti; Elmiliyani Wahyuni S; Suwardi Suwardi; Revi Candra (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This study aims to determine the effect of Islamic financial literacy on the decisions of students majoring in Islamic banking at the Faculty of Economics and Islamic Business IAIN Batusangkar in the use of Islamic banking services. This type of research is field research with an associative descriptive quantitative approach. The analysis technique uses simple linear regression. Data collection techniques using questionnaires from sample data as many as 85 people. The results showed that Islamic financial literacy had a positive and significant effect on the decisions of students majoring in Islamic banking in using Islamic banking services with a contribution of 58.9%. The rest is influenced by other variables not examined in this study